2012
DOI: 10.1002/qj.1885
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of NWP results for wintertime nocturnal boundary‐layer temperatures over Europe and Finland

Abstract: The results demonstrated a T2m bias increasing with decreasing temperature and strengthening temperature inversion. When a strong temperature inversion was observed in Sodankylä, the models underestimated it, whereas in nearneutral conditions the stratification was overestimated. Comparison of observed and modelled 3 h temperature tendencies showed that the T2m tendency in the models was on average only 17-20% of the observed one. The warm bias in T2m forecast in Sodankylä during periods of observed temperatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
70
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 76 publications
(76 citation statements)
references
References 42 publications
5
70
0
1
Order By: Relevance
“…Focusing on biases of seasonal means, our validation results include three interesting issues: (1) all three reanalyses had warm temperature biases in all seasons, (2) all three reanalyses yielded positive biases for the eastward wind component in all seasons, and (3) reanalyses mostly yielded negative biases for the northward wind component. The first issue is in agreement with many previous validation studies over snow and ice surfaces: Jakobson et al (2012) obtained similar results for the same (and other) reanalyses over the Arctic sea ice, Vihma et al (2002) observed a year-round warm bias for the ECMWF operational analyses over the Antarctic sea ice, and Atlaskin and Vihma (2012) observed that several numerical weather prediction models yielded warm biases under conditions of stable boundary layer over snowcovered boreal forest. The second and third issue are probably at least partly due to the resolution of reanalyses, which is not high enough to accurately represent the complex orography of the Antarctic Peninsula.…”
Section: Discussionsupporting
confidence: 89%
“…Focusing on biases of seasonal means, our validation results include three interesting issues: (1) all three reanalyses had warm temperature biases in all seasons, (2) all three reanalyses yielded positive biases for the eastward wind component in all seasons, and (3) reanalyses mostly yielded negative biases for the northward wind component. The first issue is in agreement with many previous validation studies over snow and ice surfaces: Jakobson et al (2012) obtained similar results for the same (and other) reanalyses over the Arctic sea ice, Vihma et al (2002) observed a year-round warm bias for the ECMWF operational analyses over the Antarctic sea ice, and Atlaskin and Vihma (2012) observed that several numerical weather prediction models yielded warm biases under conditions of stable boundary layer over snowcovered boreal forest. The second and third issue are probably at least partly due to the resolution of reanalyses, which is not high enough to accurately represent the complex orography of the Antarctic Peninsula.…”
Section: Discussionsupporting
confidence: 89%
“…Considering ABL modelling, it is well understood that the ABL schemes commonly applied in climate models and NWP yield excessive heat and momentum fluxes in the SBL (Cuxart et al, 2006;Tjernström et al, 2005), typically resulting in a warm bias near the surface (Atlaskin and Vihma, 2012). In the Arctic, Byrkjedal et al (2007) demonstrated the importance of a high vertical resolution: not surprisingly, model experiments with 90 levels in the vertical yielded much better results than those with 31 levels, the latter being typical for climate models contributing to the IPCC AR4.…”
Section: Atmosmentioning
confidence: 99%
“…Thus, the problem could be partially related to an insufficient spatial model resolution with respect to the relevant topographic features. But partially, it should be also related to the breakdown of inadequate turbulent mixing schemes for the atmospheric stably stratified boundary layer (Atlaskin and Vihma, 2012;Fernando and Weil, 2010;Mahrt, 2014;Zilitinkevich et al, 2015). These and other inaccuracies in the air quality assessment and modelling motivated the Pan-Eurasian Experiment (PEEX) community to include air pollution in the stably stratified boundary layers in the list of research priorities addressing the environmental and socio-economic challenges of the northern high latitudes (Lappalainen et al, 2016).…”
mentioning
confidence: 99%